New insights on reproductive features in Lepidonotothen nudifrons (Pisces, Notothenioidei) at the south Shetland Island, supported by physiological evidence - Novillo Estofan, Julio Manuel; Elisio, Mariano; Moreira, María Eugenia; Macchi, Gustavo Javier; Barrera Oro, Esteban
The Southern Ocean marine ichthyofauna is dominated by a unique costal demersal fish group, the suborder Notothenioidei. The nototheniid Lepidonotothen nudifrons is abundant in nearshore waters of the Scotia Arc region, where it is ecologically important as relevant prey of piscivorous predators. The knowledge of its reproductive biology arises exclusively from macroscopic and histologic descriptions of the maturation cycle. In this study, we provide for first time in L. nudifrons adult females, information on oocyte growth rate and change in testosterone (T) and estradiol (E2) plasma levels throughout their ovarian growth period in summer. Briefly, 98 specimens were caught at Potter Cove (PC), South Shetland Islands (SSI), from November to late March in the consecutive campaigns 2016/2017- 2017/2018. Histological analysis of the ovaries confirmed the macroscopic characteristic of the two distinct cohorts of oocytes: one leading clutch (Lc) of large orange vitellogenic oocytes, likely to be spawned in the upcoming reproductive season, and a second clutch of smaller whitish previtellogenic oocytes. In late March, females (n=17) had gonado-somatic index values between 13 and 20% (16.73±2.10) and total fecundity ranged between 2196 and 4652 oocytes/female (3209± 740), while Lc oocytes reached between 1.7 and 2.1 mm. The estimated Lc oocyte diameter average growth rate was 0.01 mm/day. Both, T and E2, increased together with the oocyte growing throughout the analyzed seasons. However, E2 variation was more significantly associated with the photoperiod than with the Lc oocyte size, whereas T was better associated with this last variable. Based on physiological evidence, mainly on the significant plasma level increase of both sex steroids observed in females captured in March, and also on the reproductive effort data, we suggest that: (1) specimens from March were presumably at a late vitellogenesis stage just prior to the oocyte final maturation, and thus L. nudifrons spawning period might onset in late MarchApril at ...